Towards a Knowledge Base for Network Diagnosis - Gregory, N. Vincent (1994)
In this dissertation, the domain knowledge analyzed and current techniques in troubleshooting and current expert systems in the network domain are examined. A model that will be arguably most suited for the network domain is proposed and a prototype system that will be capable of diagnosing today's complex network components is presented.